Implementasi Fatwa Dewan Syariah Nasional MUI No. 108/DSN-MUI/X/2016 tentang Pedoman Penyelenggaraan Pariwisata Berdasarkan Prinsip Syariah pada Biro Perjalanan Wisata Syariah - Sheila Distianti; Muhammad Nazieh Ibadillah (Jurnal Al-fatih Global Mulia, 2021)
The development of sharia tourism which was currently becoming a trend had progressed in recent years to bring Indonesia to become the world's best sharia tourism destination in 2019. The development of sharia tourism was considered to provide positive progress for the economy, social and culture. This was also supported by the era of technology and socialization and expansion of sharia tourism by the travel agencies by packaging the many sharia tourism packages offered such as those in Elhasana Tour & Travel. And also various government regulations and the DSN-MUI fatwa issued in 2016 indicated that the government was serious in developing sharia tourism in Indonesia. The purpose of this research was to determine the application of sharia principles in travel agencies in accordance with the DSN-MUI fatwa, to determine the driving factors and obstacles in the application of sharia principles in accordance with the DSN-MUI fatwa and to determine the effect of the application of sharia principles on business development in Elhasana Tour & Travel. This research used structured observations, documentation, and interviews to obtain the desired information more accurately. The research used a qualitative method, which was descriptive in nature by producing a more in-depth description of the sharia travel agencies.